Кургани поблизу хут. Дуканичі у пониззі Псла - Супруненко, О.Б.; Кулатова, І.М. (Археологічні дослідження в Україні, 2010)
In the outskirts of Komsomolsk in Poltava Oblast on the territory of industrial area of Yeristovka quarry of Poltava GOK Corporation near Dukanychi hamlet not far from Voloshyne village a group of barrows II consisting of four mounds, 21 burials of the Early and Late Bronze Age, a Late Sarmatian tomb, and a cemetery of the hamlet of the end of the 19th c. and the beginning of the 20th c. were studied.